A United States expert consensus to standardise definitions, follow‐up, and treatment targets for extra‐intestinal manifestations in inflammatory bowel disease. Issue 9 (11th March 2022) - Falloon, Katherine; Cohen, Benjamin; Ananthakrishnan, Ashwin N.; Barnes, Edward L.; Bhattacharya, Abhik; Colombel, Jean‐Frederic; Cross, Raymond K.; Driscoll, Marcia S.; Fernandez, Anthony P.; Ha, Christina; Herfarth, Hans; Horst, Sara; et al.
Summary: Background and aims: Extra‐intestinal manifestations (EIMs) are a common complication of inflammatory bowel diseases (IBD), affecting up to half of the patients. Despite their high prevalence, information on standardised definitions, diagnostic strategies, and treatment targets is limited. Methods: As a starting point for a national EIM study network, an interdisciplinary expert panel of 12 gastroenterologists, 4 rheumatologists, 3 ophthalmologists, 6 dermatologists, and 4 patient representatives was assembled. Modified Delphi consensus methodology was used. Fifty‐four candidate items were derived from the literature review and expert opinion focusing on five major EIMs (erythema nodosum, pyoderma gangrenosum, uveitis, peripheral arthritis, and axial arthritis) were rated in three voting rounds. Results: For use in a clinical practice setting and as part of the creation of a prospective registry of patients with EIMs, the panel developed definitions for erythema nodosum, pyoderma gangrenosum, uveitis, peripheral arthritis, and axial arthritis; identified the appropriate and optimal subspecialists to diagnose and manage each; provided methods to monitor disease course; offered guidance regarding monitoring intervals; and defined resolution and recurrence. Conclusions: Consensus criteria for appropriate and optimal means of diagnosing and monitoring five EIMs have been developed as a starting point to inform clinical practice and future trial design. Key findings include straightforward diagnostic criteria, guidance regarding who can appropriately and optimally diagnose each, and monitoring options that include patient and physician‐reported outcomes. These findings will be used in a national multicenter study network to optimise the management of EIMs. Abstract : A national multispecialty modified Delphi consensus panel was performed to standardise definitions, follow‐up, and treatment targets for five extra‐intestinal manifestations (erythema nodosum, pyoderma gangenosum, uveitis, peripheral arthritis, and axial arthritis).